Islam and peace-building in the Asia-Pacific - Mohamed Nawab Mohamed Osman (World Scientific, 2016)
"Islam and Peace-Building in the Asia-Pacific Region provides a unique backdrop of how native or migrant Muslims interact with communities of other faiths that have led to the contemporary treatment of Islam and the Muslim communities in these nations. The book is based on the theme of Islam's presence and development in the Asia-Pacific region, and the concerns faced by Muslims in the region. Section 1 details the current status of peace or conflict between Muslims and practitioners of other faiths in Cambodia, Myanmar, Thailand and the Philippines, and the role of Muslim institutions in promoting peace in each nation. Section 2 features how Muslims living in cosmopolitan areas such as Australia, Indonesia and Japan engage with people of other faiths. Lastly, Section 3 explores the concerns with the interaction of the religion, state and society in Brunei, Indonesia, Malaysia and Singapore. A unique collection of the history of Islam in the region, this book seeks to provide valuable insight for the global policy community by offering a comprehensive treatment of issues highlighted"-- Provided by publisher.